Effects of neuro-muscular training on vertical jump height: a forward dynamics simulation study - Nagano, A.; Gerritsen, K. G. M. (2000)
In several sports it is extremely important for athletes to be able to jump high. Athletes' jumping ability can be improved by training both muscular and neural factors of the neuro-muscular system. However, it is difficult to qualitatively analyze the effect of improving each parameter using experimental approaches, as there are many factors that are modified simultaneously during the course of the training programme. One of the approaches to solve this problenm is the forward-dynamics simulation method (Bobbert and van Soest, 1994). The purpose of this study was to systematically investigate the training effects of selected neuro-muscular parameters on vertical jumping performance using forward-dynamics method. Maximal isometric force, maximal shortening velocity and maximal activation signal sent to the muscles were selected as trainable parameters.